Analisis Crowdfunding Syariah Berdasarkan Prinsip Syariah Compliance Serta Implementasinya Dalam Produk Perbankan Syariah (Studi Kasus Bank Muamalat) - Lestari, Aprilia; Indra, Ahmad Perdana; Anggraini, Tuti (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This research aims to analyze the application of sharia crowdfunding in the context of sharia compliance principles and its implementation in sharia banking products with a case study at Bank Muamalat. Sharia crowdfunding, as an alternative method of funding in accordance with sharia principles, offers the opportunity to accumulate various projects or businesses while still complying with the prohibitions on usury, gharar and maisir. This research discusses the application of sharia principles in sharia crowdfunding managed by Bank Muamalat, as well as how to integrate and implement this product in their sharia banking portfolio. The research methodology uses a qualitative approach with data analysis from internal bank reports, interviews with related parties, and literature studies on sharia principles and crowdfunding practices. The research results show that although sharia crowdfunding provides an innovative alternative. The main problems identified include late payments, defaults on projects, and difficulties in maintaining strict sharia compliance. This research recommends improvements in sharia monitoring mechanisms, sharpening operational guidelines, and training for sharia crowdfunding managers to ensure better and more effective products in meeting customer needs and sharia objectives.